he Relationship between the Intensity of Playing Online Games and the Incidence of Asthenopia in Students at SMP Negeri 2 Gorontalo - Nirwanto Rahim; Moh Amin Mosi; Rosmin Ilham; Yuniar M. Soeli (PT.Mantaya Idea Batara, 2023)
Adolescence is a period of transition or transition from childhood to adulthood. Adolescent development occurs in all parts of life, including socio-emotion changes to find an identity. Playing with peers and communicating through games is mostly done by teenagers through playing online games. Online games attract the attention of teenagers because of their attractive appearance, playing style, game graphics and image resolution. Playing online games with long intensity can cause confusion between reality and illusion, affect concentration power, and will have an impact on visual disturbances. This study used a descriptive research design with a cross- sectional approach. The population in this study amounted to 115 people with a total sample of 115 respondents with a total sampling technique. The results showed that the intensity of playing online games and the incidence of asthenopia showed a value of ?-value = 0.000 (?<0.05), which means that there was a significant relationship between the intensity of playing online games and the incidence of asthenopia in students. It is hoped that for schools, this research can become a benchmark for assessing the level of intensity of playing online games and the incidence of asthenopia.